Parent-Student Communication in Dhuafa Boarding School and Its Relation to Academic Achievement - Hasna Najiyyah; Yulina Eva Riany; Irni Rahmayani Johan (Universitas Muhammadiyah Surakarta, 2024)
Dhuafa students in boarding schools face challenges in establishing quality communication with parents, which is important for their achievements. This study explores the quality and quantity of communication between parents and dhuafa students in boarding schools and the connection between parent-student communication and learning achievement. The research subjects comprised 12 students from SMP Cendekia Baznas (6 boys and 6 girls, grades 7-9). This research employs a descriptive qualitative approach. Data were collected through semi-structured interviews and analyzed using NVivo 12 Plus. The results identified four main themes: communication mechanisms, communication schedules and duration, communication constraints, and the connection between communication and achievement. Students communicate with their parents through phone calls, chats, letters, video calls, and visits. Communication occurs once a week, either on Saturday or Sunday. Communication constraints include signal issues, financial limitations, distractions, parents' availability, and limited communication time. Parent-student communication in boarding schools is positively connected to learning achievement as it enhances motivation, fosters enthusiasm for achievement, and provides spiritual and moral support to students. However, suboptimal communication duration causes some students to feel there is no significant connection between communication with parents and their learning achievement